A Phenomenological Case Study of Communication Between Clinicians About Attention-Deficit/Hyperactivity Disorder Assessment. (January 2014) - Lynch, Sean E.; Cho, Jennifer; Ogle, Stacy; Sellman, Heather; dosReis, Susan
Introduction . Communication between clinicians related to attention-deficit/hyperactivity disorder (ADHD) assessment is challenging because it involves a number of individuals. While the communication process might be more efficient if these individuals worked together, research on ADHD-specific collaborative care models is scarce. The purpose of this qualitative study was to investigate the parties with whom prescribers communicate and how they collaborate. Methods . Providers were interviewed, and the data were analyzed using a phenomenological case study approach. Results . The results suggested that there were communication breakdowns between providers and teachers that hindered the assessment process. Discussion . Communication related to ADHD assessment may be more complex than theoretical models may conceptualize.